RACHEL WEXELBAUM, ed., Queers Online: LGBT Digital Practices in Libraries, Archives, and Museums - Stanton-Hagan, Al (Archivaria, 2016)
Queers Online: LGBT Digital Practices in Libraries, Archives, and Museums. RACHEL WEXELBAUM, ed. Sacramento, CA: Litwin Books, 2015. 239 pp. ISBN 978-1-936117-79-6